Cognitive and neurobiological mechanisms of alcohol-related aggression - Heinz, Adrienne J.; Beck, Anne; Meyer-Lindenberg, Andreas; Sterzer, Philipp; Heinz, Andreas (Nature reviews. Neuroscience, 2011)
Alcohol use is implicated in approximately 50% of all violent crimes and sexual assaults in industrialized nations.Both acute and chronic alcohol intake increase the risk for alcohol-associated aggression.Only a subset of individuals who drink alcohol become aggressive, and psychological studies have identified several gender and individual differences that confer risk for alcohol-related aggression.Twin and adoption studies have shown a significant disposition towards violent behaviour only in association with an increased risk to develop alcohol dependence.Animal experiments and a limited number of studies in humans show that alcohol-related aggression is found in a subset of individuals who were exposed to social adversity and carry certain risk genotypes.Genetic and environmental factors are associated with aggressive behaviour: findings point to an important role of the serotonin system and its interactions with GABAergic neurotransmission in determining vulnerability to alcohol-associated aggression.Chronic alcohol intake impairs serotonergic neurotransmission, which (according to studies in healthy controls but not yet in patients who are alcohol dependent) modulates limbic processing of aversive stimuli and prefrontal functions associated with behavioural control.We suggest that acute alcohol intake facilitates aggression in vulnerable individuals because it impairs prefrontal executive functions, disinhibits limbic processing of threatening stimuli and elicits expectancies for alcohol-associated aggression.
Gesehen am 04.10.2022